Cost-benefit analysis of biofuel of oil-seed origin in Greece - Diakoulaki D.; Kavadakis G. (Comprehensive economic and spatial bio-energy modelling, 2002)
This paper presents a Cost-Benefit Analysis for the assessment of biodiesel in comparison with conventional diesel used in the transport sector in Greece. The analysis takes into account costs and benefits related with both marketed and non-marketed goods. The results show that based on purely financial criteria biodiesel is hardly competitive to oil products and that the overall economic performance of such an investment depends highly on the prices of both, raw materials and by-products. However, from a social point of view the introduction of this alternative energy source in the transport sector is extremely desirable and this calls for promoting economic incentives and other policy measures aimed at encouraging producers to be involved in such kind of activities.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)